Kręgi sąsiedzkie: studium miejskiego sąsiedztwa we współczesnej Polsce, główne ustalenia - Nowak, Marek; Pluciński, Przemysław; Siatkowski, Andrzej (Człowiek i Społeczeństwo, 2019)
The article presents the problems of urban neighbourhood organized regarding its theoretical and empirical nature. It presents both the history and the theoretical discussion of neighbourhood research, especially within the frames of Polish sociology, although not exclusively, as well as empirical results of the latest research conducted in three cities of different size (Warsaw, Poznań, Wronki) in 2019. Partial results of the research presented in the article focus on factors conducive to building neighbourly relations. Marek Nowak, Przemysław Pluciński, Andrzej Siatkowski, Neighbourhood Circles: The Study of Urban Neighbourhood in Contemporary Poland and Its Basic Outcomes [Kręgi sąsiedzkie: studium miejskiego sąsiedztwa we współczesnej Polsce, główne ustalenia] edited by M. Nowak, “Człowiek i Społeczeństwo” vol. XLVIII: Kuchnia badań miejskich. Studia na temat praktyki empirycznej badaczy miasta [A backstage of urban research], Poznań 2019, pp. 55–73, Adam Mickiewicz University. ISSN 0239-3271. Marek Nowak, Uniwersytet im. Adama Mickiewicza w Poznaniu, Wydział Socjologii, ul. Szamarzewskiego 89, 60-568 Poznań, e-mail: marek.nowak@amu.edu.pl Przemysław Pluciński, Uniwersytet im. Adama Mickiewicza w Poznaniu, Wydział Socjologii, ul. Szamarzewskiego 89, 60-568 Poznań, e-mail: plucin@amu.edu.pl Andrzej Siatkowski, Centrum Badań Społecznych Fundacji UAM, ul. Szamarzewskiego 89, 60-568 Poznań, e-mail: andrzej.siatkowski@amu.edu.pl